RELATIONSHIP BETWEEN BREAKFAST AND THE LEVEL OF ANXIETY ON GRADE 6 FEMALE STUDENTS OF PATRANG III, IV, AND V PUBLIC ELEMENTARY SCHOOL JEMBER WHEN EXPERIENCING MENARCHE - Annisa Nurida; Sujono Kardis; Eva Rosita Dewi (Universitas Muhammadiyah Surabaya, 2023)
The purpose of this study is to see whether there is a relationship between breakfast and the level of anxiety on the female students when they experience menarche.The design of this study was quantitative correlation with cross sectional data collection. The sample was taken by using